THE INFLUENCE OF VARIOUS COLLABORATIVE ASPECTS OF LARGE AND MEDIUM COMPANIES ON REGIONAL PERFORMANCE - Cosmin Florin LEHENE; Răzvan Liviu NISTOR (Annals of the University of Oradea: Economic Science)
In this paper we investigate a modern topic in the regional economics literature, namely the concept of microeconomic competitiveness. Particularly, we investigate the influence of the collaborative activities of the large and medium firms, as a regional prerequisite for cluster formation and development, and the relationship with various regional level performances. For years already, scholars debated within the economics literature if the regional clusters drive the regional performance. Therefore, we contribute to this stream of research through investigating if the specific conditions in the regional context, in our case the collaborative aspects of the companies operating in the region, influence the regional performance. Through a statistical analysis of the data provided by 40 best performers medium and large companies, operating in three regions for economic development in Romania, we found significant associations between the proposed variables. Specifically, we found that the regions in which the companies reported higher scores for proactivity regarding collaboration identification and formation, higher commitment for collaboration participation, respectively higher scores for their collaborative competences and abilities are the regions which also reported higher regional level performances. The results from our study are valuable for the regional economics literature since underline the fact that in order to build regional competitiveness, respectively to accelerate the economic growth and development, the existent companies operating in the regions also need to take some specific actions. The companies and firms play an important and active role in the regional economic development. In contrast to a ‘orthodox’ top-down approach for economic development, the paper brings support to the stream of research on regional economics which militates for collaboration between the public and private sector, and for regional development through microeconomics competitiveness building, local and regional.